Revisão sistemática do perfil de risco e profilaxia de tromboembolismo venoso no Brasil e no mundo - Carandina, Rafael Factor [UNESP] (2015)
Context: The pharmacological and mechanical prophylaxis of venous thromboembolism (VTE) are already well established in international consensus, based on specific models for risk stratification. However, in approximately 50% of cases admitted in hospitals in Brazil and the rest of the world, patients do not receive appropriate prophylaxis. Objectives: Present work conducts a systematic review and meta-analysis of comparative results of the risk profile and inadequate prophylaxis of patients admitted to hospitals in Brazil and in the world and countries with HDI above and below 0.8. Methods: We searched for articles published in any language between 2000-2014 in electronic databases: Biblioteca Virtual em Saúde (BVS), PUBMED, SciELO, EMBASE and LILACS. The reference lists of articles were also examined for eligible studies. The search strategy was directed to Cross-Sectional Studies about the risk profile of patients and adequacy of prophylaxis strategies adopted by international guidelines for Venous Thromboembolism, according to the following PICO: P - clinical or surgical patients in hospitals; I - Prevention; C - Brazil vs. World Comparison and HDI <0.8 and HDI> 0.8; O - Inadequacy of prophilaxis. The selection of the articles and data extraction were performed by two independent authors. The presentation of the data in the articles, as well as types of patients, medical specialties involved, hospital profile, inclusion / exclusion criteria, sample size, proportion of men and women, risk score used, conflict of declaration of interests were variable and were considered as possible sources of heterogeneity and biases. Individual data of inadequate prophylaxis studies in Brazil and the rest of the world, as well as countries with different HDI were inserted separately into a statistical program that did a proportional metaanalysis (StatsDirect) using the random effects model. Frequencies and confidence intervals were used in ...